Urban Nature Between Modern and Postmodern Aesthetics: Reflections Based on the Social Constructivist Approach - Kühne, Olaf (Quaestiones Geographicae, 2012)
The article deals with the question of the social construction and assessment of physical urban objects (such as trees, gardens, parks) which are perceived as natural. The society perceives nature ambivalently. Nature describes "the primary and the good (…) that contrasts with society as the artificial and even the destructive". Nevertheless nature means "the wild and the threatening which is domesticated to protect society" (Groß 2006: 5). In the city, nature exists in a domesticated form (e.g. as a park) or in a less domesticated condition (e.g. as sparse flora). Modernity and postmodernity have different implications in the perception and assessment of urban nature. Especially the less domesticated nature contradicts the modern aesthetic scheme. It is assumed that the antagonism of legitimated and trivial culture is a substantial characteristic of modernity, which incorporates itself in a series of fundamental dichotomies like nature and culture (Fuller 1992). A typical characteristic of the modern dichotomy is the construction of order and disorder. By contrast, postmodern aesthetics challenges and deconstructs these dichotomies (Sloterdijk 1987, 1988). Unlike modernity, postmodernity tolerates the less domesticated nature in cities which includes new possibilities of the composition of the cityscape, especially for ruined buildings and areas. Postmodern landscape planning and architecture do not mean ‘anything goes’, but rather including the pluralism of citizens' interests, belongings and needs, especially because they are the sovereigns in democratic societies. In consequence, the postmodern perspective on planning can be an integral part of the sustainable development of cities.